Marriage in the Western Church : the Christianization of marriage during the patristic and early medieval periods - Reynolds, Philip Lyndon, 1950- (Boston. Brill Academic Publishers, Inc., 1994)
Author Philip Reynolds examines how marriage acquired a specifically Christian identity in the Latin West during the first millennium after Christ. Beginning with Jesus, everything the Christians did, including getting married, began a process of differentiation. Reynolds offers three themes for theological reflection and interpretation: Jesus'
Marriage in civil law -- Marriage in the church -- Augustine's theology of marriage -- The nuptial process -- Marrying in the Frankish church.
Originally published: Leiden ; New York : E.J. Brill, 1994.
Includes bibliographical references (pages 420-427) and index.
Keywords: Marriage -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600.; Marriage -- Religious aspects -- Christianity -- History of doctrines -- Middle Ages, 600-1500.